Comments on the article "possible contribution of129I in the drinking water and food supply to the nodular formation of thyroid tissue" [1] (multiple letters) - Brooks, Antone L.; Dogru, Mahmut; Cigna, Arrigo A. (My University, 2005)
[Abstract Not Available]
Keywords: Food Contamination, Radioactive; Food Supply; Humans; Iodine Radioisotopes; Thyroid Nodule; Water Supply; drinking water; iodine 129; catering service; half life time; letter; priority journal; qualitative analysis; radiation dose; radioactive contamination; radioactivity; risk assessment; thyroid nodule